What happens when the definition of disability changes? The case of obesity - Jennifer Bennett Shinall (IZA Journal of Labor Economics, 2016)
This paper examines how Congress's 2008 expansion of who is disabled under the Americans with Disabilities Act (ADA) impacts the labor market outcomes of newly covered individuals. Focusing on obese individuals, I exploit variation in coverage of obesity before and after the 2008 expansion to identify effects of the legal change, but I find no improvement in the labor market outcomes of the obese. Although the 2008 expansion was intended to remedy the unintended consequences of the ADA and improve labor market outcomes of the disabled, these early estimates suggest that the expansion has not yet achieved Congress's stated goals.
Keywords: J14; J21; J78; K31; 330; ADA; Disability law; Obesity; Employment discrimination; Law in action